Helminth Parasites of Invasive Freshwater Fish in Lithuania - Kudlai, Olena; Rakauskas, Vytautas; Baker, Nathan Jay; Pantoja, Camila; Lisitsyna, Olga; Binkienė, Rasa (Animals, 2024)
Freshwater ecosystems in Lithuania are threatened by the introduction of invasive fish species including Neogobius fluviatilis, N. melanostomus, Perccottus glenii, and Pseudorasbora parva. Data on helminth parasites of these fishes have not been comprehensively studied, with only two reports on parasites of N. melanostomus from the Curonian Lagoon and Baltic Sea, Lithuania. We examined 278 fish individuals representing 4 invasive species from 13 waterbodies. Using morphological and molecular analyses, we identified 29 helminth taxa representing 15 digenean trematodes, 6 nematodes, 4 cestodes, 2 acanthocephalans, and 2 monogeneans. With 18 species, N. fluviatilis had the highest helminth diversity, followed by N. melanostomus (11 species) and Ps. parva (8 species). Perccottus glenii was found to be free from helminth infection. The availability of historical information on the native fish parasites in Lithuania allowed us to conclude that out of the 29 recorded species, invasive fish serve as hosts for 22 local fish helminth species, while 7 helminth species have been reported exclusively in invasive fish. Based on newly obtained and previously published data, a total of 34 helminth species parasitise invasive fish in Lithuania, of which 30 use these fish as intermediate or paratenic hosts.
Keywords: morphological and molecular identification; aquatic invasion; Perccottus glenii; Neogobius spp.; Pseudorasbora parva; Baltic freshwater ecosystems